(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objectives: To evaluate the antimicrobial activity of medicinal plants against human pathogenic bacteria and perform Minimum Inhibitory Concentration (MIC) of plants extracts. Methods: Rhizome of Curcuma longa, dried buds of Synzygium aromaticum, seeds of Zanthoxylum armatum and leaves of Elaeocarpus ganitrus, Psidium guajava, Azadirachta indica, and Artemisia vulgaris were collected from hilly regions of Nepal. The plant parts were air-dried at room temperature for several days and grinded to powder form. The ethanolic extracts of medicinal plants were prepared by using the percolation process of extraction using separating funnel and tested against human pathogenic bacteria by disc diffusion method. Then, Minimum Inhibitory Concentration (MIC) of the plant extracts were performed. Results: All plants extracts exhibited antibacterial properties against bacteria under study. However, extract from S. aromaticum (Clove), P. guajava (Guava) and E. ganitrus (Rudraksh) leaves showed most promising result against Staphylococcus aureus with zone of inhibition of 14mm, 16mm and 16 mm respectively. Likewise, S. aromaticum (Clove), C. longa (Turmeric) and P. guajava (Guava) showed good antibacterial activity against Escherichia coli with zone of inhibition of 11mm, 11mm and 10mm respectively. A. vulgaris (Titepati) and A. indica (Neem leaves) showed promising activity against Pseudomonas aeruginosa with zone of inhibition of 11mm. Z. armatum (Timur) showed good result against E. coli with zone of inhibition 10mm. MIC values of ethanolic extracts of S. aromaticum and E. ganitrus were found to be at the range of 12.5-25mg/ml. Conclusion: This study has helped to understand the use of these plants as traditional medicine in an economic and safe alternative to treat infectious diseases.